From Regulation to Competition: New frontiers in electricity markets - Einhorn, Michael A. (Springer Netherlands, 1994)
Electric utilities throughout the world continue to face new challenges involving ownership, market structure, and regulation. There are three related issues at hand. First, should ownership be private or public? Second, what operations should be integrated and where is competition feasible? Third, where is regulation necessary and can it be made more efficient? This volume bears directly upon these concerns. The book contains two sections. The first six articles discuss the British electricity experiment that has privatized and disintegrated the nation's generation, transmission, and distribution companies, introduced market competition for power purchases, and implemented incentive regulation for monopolized transmission and distribution grids. The remaining articles focus on the theater in which significant microeconomic issues will continue to emerge, most immediately in the U.K. and U.S.A. -- the coordination and pricing of transmission